DEVELOPMENT OF LESSON TRAININGS ON THE BASIS OF MODULE TECHNOLOGY (American Journal of Interdisciplinary Research and Development, 2022)
The main purpose of the education system is to form a professionally mature person in all areas, to develop his knowledge, skills and abilities, as well as to train a competitive specialist. Analysis of foreign experience shows that the development of society depends on the development and improvement of innovative technologies introduced in the field of education. In order to improve this process, it is important to organize training sessions on the basis of innovative approaches to teaching and modular learning technology, which is an integral part of it, and thus increase the quality and effectiveness of education.